Pengaruh Kepemimpinan Pelayanan, Motivasi Intrinsik Dan Dukungan Sosial Terhadap Komitmen Organisasi - Devia, Elfanindi; Prayekti, Prayekti (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aims to determine the effect of Service Leadership Influence, intrinsic motivation and social support on the organizational commitment of the Study at the Sleman Regency Social Service. This study uses a nonprobability sampling technique using a saturated sampling method. The population for this study were employees of the Sleman Regency Social Service. The sample used was 50 respondents. The test instruments used in this study were validity and reliability tests. The data collection technique used a questionnaire. The data analysis technique used in this research is descriptive analysis. The results showed that service leadership had a positive effect on organizational commitment, intrinsic motivation had a positive effect on organizational commitment, and social support had a positive effect on organizational commitment. Keywords: Servant Leadership, Intrinsic Motivation, Social Support, Organizational Commitment